How to be a superhero: stories of creating a culture of inclusion through theatre - Jaskolski, Kaitlin Orlena-Kearns (Department of Drama, 2022)
This thesis investigates the use of Inclusive theatre to disengage the ‘disabled'/ ‘non-disabled' binary for transformation to inclusive cultures. The research extends existing scholarship in Inclusive and applied theatre practices by documenting selected case studies in west and southern Africa. A sociocultural lens defines disability as a social construct, problematizing community reactions, systemic oppression and societal barriers as the disabling force rather than any physical or cognitive impairment. A series of participatory action research projects explore inclusion through an applied theatre praxis and critical/performance ethnography. Progressive pedagogy informs the methods, ethics, and values of each cross-cultural inclusive project. Participants with neurodivergent, or atypical (dis)abilities are contextualized as heroes within the metaphoric framework of the hero's journey as popularized by Joseph Campbell. Campbell's stages are juxtaposed with project workshops and performances to emphasize the universal application of inclusion, and the educational power of storytelling. The primary journey follows the development of Nigeria's premier inclusive theatre company; from drama-as-therapy beginnings to their professional performance of How to be a Superhero: A Guide to Saving the World. Supplementary projects with Hijinx Theatre in Lesotho and the Oasis Association in South Africa provide stories of igniting hidden talents and overcoming the obstacles that create barriers to inclusion in both the arts and society. An enabled dramaturgy details accessibility, authenticity, engagement, transformation, and aesthetics to debate the allies/enemies of inclusive theatre. Each project reveals the boons of adapting practices through considerations of accessibility, accommodations, and modifications. The culminating performances of each project provide evidence that storytelling, building relationships, transforming and engaging participants and audiences through theatre forges empathy, increases representation, and encourages visibility. Psychologist Philip Zimbardo argues that “Heroism can be learned, can be taught, can be modeled, and can be a quality of being to which we all should aspire.” (2011). This research, inspired by Campbell and Zimbardo, argues that inclusion, like heroism, can be learned, taught and modeled through theatre to create a culture of inclusion.